Yeast populations on the tropical timber tree species Milicia excelsa - Hong, Li; Veenendaal, E.; Ab Shukor, Nor Aini; Cobbinah, J. R.; Leifert, Carlo (Wiley, 1995)
Yeast populations found on the tropical timber tree species Milicia excelsa showed very little diversity at the genus and species level. Of 62 isolates, 87% were Cryptococcus laurentii, 5%Candida humicola, 3%Candida curvata, 1.5%Candida membranaefaciens, 1.5%Rhodotorula minuta and 1.5%Rhodotorula rubra. Approximately half of the Crypt. laurentii strains had unusual metabolic profiles when compared with the Crypt. laurentii strains in the profile library of the APILAB yeast identification software. All isolated strains were non-pathogenic and did not show antagonism against Botrytis cinerea in an in vitro plate assay. However, three strains of Crypt. laurentii suppressed disease development of B. cinerea in a leaf disk bio-assay. This indicates that protection of leaves against opportunistic fungal diseases may be part of the ecological function of Crypt. laurentii populations on Milicia leaves and the potential of this yeast species for biological control.